Ana Dhei Dhato: A Traditional Wedding Tradition at Rajawawo Village of Ende Regency - Wendelinus Janggo (Bina Nusantara University, 2021)
The research aimed to describe each process of ‘Ana Dhei Dhato’ and revealed its cultural meanings based on the perspective of people in Rajawawo village of Ende regency. The research applied a descriptive qualitative. In collecting data, interviews, note-taking, and recording were conducted. The data were analyzed through transcribing and translating. The analysis results show that ‘Ana Dhei Dhato’ is considered the most valuable type of wedding because of its complexity and peculiar characteristics. It can be seen from the way they run this kind of wedding ritual. Some cultural meanings are found in these wedding rituals and language spoken, such as religious meaning, social meaning, historical meaning, juridical meaning, and didactic meaning. Therefore, it is expected that people in Rajawawo village must consider ‘Ana Dhei Dhato’ as one of the most valuable cultural heritages and should also maintain its existence.